AWARENESS FOR BETTER ADAPTATION STRATEGY DEVELOPMENT FOR CLIMATE CHANGE IMPACTS IN PAKISTAN (Pakistan Journal of Science, 2015)
Climate change awareness has become very important to develop adaptation strategies for climate change impacts. Climate change impacts varied in type and intensity for different countries, but the lack of awareness is making developing countries more vulnerable to the alarming impacts of climate change. The purpose of this study was to explore the level of awareness to make adaptation strategy for climate change impacts in Lahore, Pakistan. Relevant literature on climate change awareness revealed that climate change awareness in Pakistan was very low. The findings of this paper were based on a detailed survey conducted with the general public of Lahore. This research paper was attempted to find out the existing level of climate change awareness for making better adaptation strategy in Lahore
Keywords: Climate Change; Awareness; Adaptation; Impacta; Strategy Development